Hepatitis A virus infection and seroprevalence, Istanbul, Turkey, 2020-2023 - Mehmet Karabey; Sema Alacam; Nuran Karabulut; Hayriye Uysal; Alper Gunduz; Ozlem Altuntas Aydina (Annals of Saudi Medicine)
BACKGROUND: Hepatitis A infections continue to be a major global public health problem. The epidemiology and seroprevalence of hepatitis A virus (HAV) have important public health implications. This study aimed to retrospectively examine the hepatitis A cases and hepatitis A seroprevalence in our region in our hospital with the highest number of inpatient and outpatient cases in Istanbul. OBJECTIVE: Determination of hepatitis A cases and seroprevalence. DESIGN: Cross-sectional. SETTING: Tertiary care. PATIENTS AND METHODS: A total of 39 385 individuals who were tested for Anti-HAV IgM and Anti-HAV Total (IgM+IgG) antibodies between May 2020 and September 2023 and were included in this study. Hepatitis A specific IgM and Total (IgM+IgG) antibodies were determined using the enzyme-linked immunosorbent assay method. MAIN OUTCOME MEASURE: Hepatitis A seroprevalence. SAMPLE SIZE: 46 721 RESULTS: The study included a total of 46 721 samples from 39 385 individuals who were tested for hepatitis A serology. The median age of the 39385 individuals included in the study was 28 (interquartile range [IQR]; 22–46), with 58.74% being female and 4.07% (n=1163) being foreign nationals. Reactivity was detected in 91 of the 25 442 patients tested for HAV-IgM. Among these patients, 33 (0.13%) had acute hepatitis A infection, while 58 (0.23%) were considered false positives. Of the acute hepatitis A patients, 13 (0.09%) were women, and 22 (0.80%) were children. Acute hepatitis A was most commonly observed in the 6–9 and 15–18 age groups, with 7 cases each. The seroprevalence rate of hepatitis A was 67.23% among 33 683 individuals. Of those tested for HAV-Total, 13 132 (64.92%) were women, and 2533 (64.88%) were children. The lowest seroprevalence rate among age groups (35.91%) was in the 15–18 age year range, while the highest seroprevalence (98.34%) was detected in individuals aged 60 years and above. CONCLUSION: With a seroprevalence rate of 67.23%, our region is still considered a medium-endemic area for hepatitis A, and it is crucial to continue administering the HAV vaccine as currently included in the childhood vaccination schedule in our country. Additionally, the significantly low hepatitis A seropositivity, particularly in the 15–18 and 19–24 age groups, indicates the need to promote catch-up vaccination for young adults. Since our study covers a large population, it can serve as a guide regarding the serological status of hepatitis A in Istanbul. LIMITATIONS: Since vaccination information for the study population was not available, it was not possible to distinguish between seropositivity due to vaccination or natural immunity. Despite being conducted in Istanbul, a cosmopolitan city, and in the largest city hospital, the results may not be representative of the entire country.